Comparative Evaluation of Diagnostic Performance of Circulating free DNA by Conventional vs. Real Time PCR in Gallbladder Cancer - Kumari PhD, Swati; Mishra PhD, Sridhar; Agarwal MD, Akash; Pandey MD, Anshuman; Sonkar MD, Abhinav; Husain MD, Nuzhat (International Journal of Innovative Research in Medical Science, 2022)
Background: Circulating free DNA (cfDNA) in serum/plasma has been studied as a promising biomarker in various pathologies, including cancer. However, there is no standardized method for the isolation and quantification of serum cfDNA. An effective and reliable method for isolation and quantification is of utmost importance before any clinical decision. The current study compares the conventional and real-time PCR methods to find any differences and concordance in cfDNA levels between the two methods and the diagnostic accuracy of cfDNA by each method. Methods: Serum sample was collected from 67 subjects, including 17 normal healthy individuals (control, n=17), 19 disease controls (cholecystitis, n=19), and 31 Gallbladder cancer patients (cancer, n=31) before any treatment for cfDNA quantification. Results: The cfDNA level did not differ significantly between two methods in both control and cholecystitis groups. In cancer group, cfDNA level was significantly (P < 0.001) different and higher in real time PCR as compared to conventional PCR. There was no significant correlation between two methods in control (r=0.02, P = 0.937), cholecystitis (r=0.10, P = 0.697), cancer (r=-0.08, P = 0.657) and total cases (control + cholecystitis + cancer) (r=0.06, P = 0.622). The diagnostic accuracy of two methods was found similar (P > 0.05) when assessed between control vs. cholecystitis (Z=0.85, P = 0.397), and control vs. total cases (Z=1.35, P = 0.177). However, the diagnostic accuracy of real time PCR was found significantly different and higher as compared to conventional PCR when assessed between control vs. cancer (Z=2.98, P = 0.003), and cholecystitis vs. cancer (Z=4.41, P < 0.001). Conclusion: Quantitative real-time PCR method is of high accuracy, reproducibility, and time-effectiveness. The diagnostic accuracy of real-time PCR was higher compared to conventional PCR.